Urban Middle Schoolers’ Experiences of an Outdoor Adventure Education Program to Facilitate Social and Emotional Development - Cian L. Brown; Benjamin C. Heddy; Kanvarbir S. Gill; Jakob Gowell; Alison C. Koenka (Education Sciences, 2025)
Middle school students face significant transitions and often do not receive education on important social-emotional learning (SEL) skills. To address this issue, we investigated how middle school students experience an outdoor adventure education program focused on SEL development. Nine students from an urban public charter school participated in the ROVER program, which taught the following SEL skills: resilience, risk management, self-efficacy, self-regulation, and emotion regulation. Students then applied these concepts through adventure sports and were instructed to translate the lessons to their home and school lives. Students completed weekly reflections to explore how students experienced this piloted program. A Structure Tabular-Thematic Analysis (ST-TA) approach was used to investigate thematic coding of reflections. Prominent themes uncovered across the reflections were emotion regulation, experience intensity, social influences, resilience, and self-preservation. We describe program implementation and discuss how using adventure sports after-school programs can impact urban middle school students’ SEL skills development. Implications suggest potential benefits of directly teaching and applying SEL competencies.